Interfacial tension of crude oil-brine systems in the Niger Delta (2012)
Interfacial tension in crude oil - brine systems is becoming very important with increasing global efforts for increased oil reserves from enhanced oil recovery projects. Interfacial tension has direct impact on multiphase flow and displacement processes in porous media. It also affects the behaviour of oil field emulsions. Most published two-phase flow and displacement processes carried out under different interfacial tension have been performed for either oil-gas or water-gas two-phase systems. This work investigated the effect of salinity, temperature and oil viscosity on the interfacial tension of oil brine systems from five different Niger Delta reservoirs. The results show that there is a strong relationship between temperature, salinity, oil viscosity and interfacial tension in heavy crude-brine systems (R2 ˃ 0.88 and P ˂ 0.05), between temperature, salinity and interfacial tension in light crude-brine systems (R2 = 0.91 and P ˂ 0.05), but no conclusive relationship in medium crudes-brine systems.